Limited access to education for child labors: A study of Bangladesh's Khulna City - Karim, Syed Nawshadul; Sultana, Taslima Marzia; Hossain, Md. Zahid; Haque, AKM Mahmudul; Hossain, Imran (Jurnal Sosiologi Dialektika, 2024)
Child labor is a prevalent issue in Bangladesh, depriving many children of educational opportunities. This study examines the impact of child labor on education. Apart from that, this study also explores various factors such as socio-cultural, economic, environmental, and psychological impacts. This study uses qualitative research methods cross sectional and the study was conducted using primary data. Interviews are conducted with focusing on ten teenagers, including nine boys and one girl. This study clarifies the points influencing the accessibility to education, which are the impacts of child labor. The findings shed light on the challenges in accessing education caused by child labor and can inform social development projects, NGOs, and government initiatives. This study concludes that the importance of emphasizing of collaboration among stakeholders to ensure universal access to quality education. It also suggests that the findings can guide future research and policy development to address child labor and improve educational accessibility.